Unconventional English in a conventional setting: the genesis and joy of the New Partridge Dictionary of Slang and Unconventional English - Victor, Terry (Alicante Journal of English Studies / Revista Alicantina de Estudios Ingleses, 2011)
This article is a personal reflection on the pivotal role of Eric Partridge, how his personality and experience shaped his lexicography, and how the inherited ‘spirit’ of Partridge is invested in the new dictionaries that bear his name. An online version is to be published alongside an updated second edition of the New Partridge Dictionary of Slang and Unconventional English (Dalzell and Victor 2012) now in preparation. The process of translating an established dictionary model to a digital environment is not without technical challenges but these are outweighed by new opportunities to gather and define previously unclassifiable items.